Comparative distributions of RSBN1 and methylated histone H4 Lysine 20 in the mouse spermatogenesis. - Youtao Wang (Public Library of Science (PLoS), 2021)
During spermatogenesis, nuclear architecture of male germ cells is dynamically changed and epigenetic modifications, in particular methylation of histones, highly contribute to its regulation as well as differentiation of male germ cells. Although several methyltransferases and demethylases for histone H3 are involved in the regulation of spermatogenesis, roles of either histone H4 lysine 20 (H4K20) methyltransferases or H4K20 demethylases during spermatogenesis still remain to be elucidated. Recently, RSBN1 which is a testis-specific gene expressed in round spermatids was identified as a demethylase for dimethyl H4K20. In this study, therefore, we confirm the demethylase function of RSBN1 and compare distributions between RSBN1 and methylated H4K20 in the seminiferous tubules. Unlike previous report, expression analyses for RSBN1 reveal that RSBN1 is not a testis-specific gene and is expressed not only in round spermatids but also in elongated spermatids. In addition, RSBN1 can demethylate not only dimethyl H4K20 but also trimethyl H4K20 and could convert both dimethyl H4K20 and trimethyl H4K20 into monomethyl H4K20. When distribution pattern of RSBN1 in the seminiferous tubule is compared to that of methylated H4K20, both dimethyl H4K20 and trimethyl H4K20 but not monomethyl H4K20 are disappeared from RSBN1 positive germ cells, suggesting that testis-specific distribution patterns of methylated H4K20 might be constructed by RSBN1. Thus, novel expression and function of RSBN1 could be useful to comprehend epigenetic regulation during spermatogenesis.